Muscular pressure pain threshold and influence of craniocervical posture in individuals with episodic tension-type headache - Stroppa-Marques, Ana Elisa Zuliani [UNESP] (2017)
Objective: The objective of this study was to analyze the pressure pain threshold (PPT) of the sternocleidomastoid (SCM), suboccipital (SO) and upper trapezius (UT) muscles and the craniocervical posture in individuals with episodic tension-type headache (ETTH). Methods: This study was a cross-sectional, non-randomized study with 60 young adults (77% female) comprising both sexes and an age range of 18-27 years. Individuals were distributed into a control group (G1) and individuals with ETTH (G2). The frequency of headaches per month was recorded. A pressure dynamometer was used to evaluate the PPT. Photogrammetry was used to evaluate the cervical lordosis (CL) and cephalic protrusion (CP). The data were statistically analyzed. Results: There were differences in the PPT, where the UT, SO and SCM muscles presented lower sensitivity to pain, respectively. The SCM muscle presented a lower PPT in G2. The CL and CP angles were significantly lower in G2. Conclusion: Individuals with ETTH exhibited a significantly lower PPT in the SCM and SO muscles than in the UT muscle. Nevertheless, individuals with ETTH presented with the SCM muscle being more sensitive to pain as well as higher CL and CP than individuals without symptomatology.